Evaluation of an internet of things device for isothermal molecular detection. - Weidmann, Manfred; Alvarez, Jesus Bueno; Zinn, Steffen; Ibragimov, Ruslan; Hasani, Mohammed; Graf, Elena; Weber, Aiko; Arrey, Frida; Szczygiel, Marcelina Marta; Kowalewska, Zuzanna; Kobialka, Rea Maja; Ceruti, Arianna; et al. (Infection, 2025)
We describe a low-cost up scalable molecular test platform providing accessibility to frequent testing - the prerequisite to control infectious epidemics. The device uses the Multi-Spectral Digital Sensor AS7341 in a small fluorescence spectrometer which communicates with a Smartphone App via Bluetooth, which passes on the raw data to outsourced computation in the cloud via the internet. This very stable setup allows easy to use on site testing of individual samples and anonymised data analysis while providing the basis for direct result transmission of a rapid isothermal molecular diagnostic test result not only to the user but also to public health bodies. This internet of things (IoT) platform allows to collect real molecular test data from users with usability and industrial up scalability at the heart of the design. The device characteristics are described in detail and the performance for a rapid SARS-CoV-2 Recombinase Polymerase Amplification assay achieved 98.6% sensitivity and 98% specificity testing 148 positive and 501 negative samples.